(untitled) (Bangladesh Journal of Animal Science, 2023)
This study was carried out to evaluate the effect of the duration of storage of ISA brown eggs at room temperature on the nutritional composition and quality of eggs. A total of one hundred and twenty (120) freshly laid eggs by 36 weeks old ISA brown layers were randomly collected and stored at room temperature for 21 days. On each sampling day (at week 0, week 1, week 2, and week 3 of storage), 30 eggs were broken to determine internal and external egg quality traits, proximate composition, and mineral profile. Collected data were subjected to statistical analysis. Duration of storage had a significant effect (p<0.05) on egg traits, proximate components, and mineral profile except for egg shape index and shell thickness. The overall egg weight, egg length, egg width, shape index, shell weight, shell ratio, and shell thickness were 56.82g, 5.69mm, 4.43mm, 78.02, 7.45g, 13.11, and 0.28mm respectively, while yolk height, albumen height, yolk weight, albumen weight, albumen ratio, yolk ratio, and Haugh unit were 13.55mm, 4.97mm, 16.32g, 33.06g, 58.11, 28.82 and 67.50% respectively. The overall means for moisture, crude protein, ash, fat, and carbohydrate were 76.27%, 12.06%, and 1.83%, 4.62%, and 4.37% respectively. Most of the minerals increased in value as the eggs increased in age. The duration of storage of eggs affected the egg quality, proximate components, and mineral profile as these parameters determine acceptability by consumers. Bangladesh Journal of Animal Science 52 (1): 15-21, March 2023